FABRICATION OF SUPERCAPACTOR CELLS WITH ELECTRODES FROM ACTIVATED CARBON MIXED WITH CARBON BLACK AND MWCNT - Asta Jaya Mulya, Marga
This research is about supercapacitor that has varied electrodes and observe the effect of varied electrodes. Variations of the electrodes are electrodes with commercially activated carbon, as Gumulya did in 2019, electrodes with activated carbon - carbon black as in the research conducted by Jasni in 2019, activated carbon electrodes - MWCNT as did Rana et al in 2019 and the heat treatment process on activated carbon as Gurten and Aktaz did in 2020. The method of applying electrodes to the current collector and cyclic voltammetry (CV) testing that carried out by Gumulya is used in this research. In this study, the constant current discharge (CCD) characterization method was also carried out to obtain the specific capacitance and equivalent series resistance (ESR) values. To observe the electrolyte response to other supercapacitor constituent materials during the charging and discharging process, a CV test was carried out on one electrode first. Current collector materials use aluminum, graphite rods and stainless steel mesh. Electrolytes using NaCL and KOH with variations of 1M, 3M and 5M concentration. The binder material uses polyvinyl alcohol (PVA) with variations of 10%, 20% and 30% of the total weight of the electrode. All variations will be tested, the results will be observed and compared to the research results mentioned above. From the results of the research that has been done, it can be concluded that the best specific capacitance results obtained in samples with treated activated carbon electrodes - carbon black with specific capacitance obtained through CCD test is 3.65 F/g, ESR is at 30?, power density is 7.8 W/kg and energy density is 0.132 Wh/kg. Graphite material can be used as a current collector in supercapacitors. Current collectors from aluminum material should be used in supercapacitors with electrolytes with a neutral pH and do not contain water. Water in the electrolyte limits the voltage window due to the separation between hydrogen and oxygen. Heat treatment on activated carbon is proven to be able to increase the capacitance of the supercapacitor sample. The addition of carbon black as much as 10% of the total weight of the iv electrode is proven to increase the conductivity and increase the specific capacitance and the addition of MWCNT is also able to enhance specific capacitnace and conductivity, although the enhancement are not as high as carbon black. The difficulty of attaching MWCNT to the current collector is suspected to be the cause of this phenomenon. When compared to the research that has done by Gumulya and Rana, this result is better even though there are differences in the materials used. The binder used by Gumulya is PVDF with a ratio of 10% of the total weight of the electrode. When compared with the results of research conducted by Inal and Jasni, the specific capacitance in this study is still much lower. This can happen because of the activated carbon material used in the two studies has a larger area than the activated carbon used in this study. In addition, the difference in the weight of the electrode sample may also seems to have an effect, in this study the total weight of the electrode in the sample with the best test results was 0.38 g, while in all papers cited the weight of the electrode was below 0.1 g.